2005
DOI: 10.1016/j.jacc.2005.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Communications of the Hand in Patients Being Considered for Transradial Coronary Angiography

Abstract: After 30 min of RA occlusion, patients with an abnormal AT showed significantly reduced blood flow to the thumb and increased thumb capillary lactate (compared with patients with a normal AT) suggestive of ischemia. Transradial cardiac catheterization should not be performed in patients with an abnormal AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 23 publications
(23 reference statements)
0
41
0
2
Order By: Relevance
“…The radial artery is larger than the ulnar in 51% of patients. 43 Greenwood et al 19 found that a longer Allen test time is associated with larger radial and smaller ulnar artery size.…”
Section: Sheath Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The radial artery is larger than the ulnar in 51% of patients. 43 Greenwood et al 19 found that a longer Allen test time is associated with larger radial and smaller ulnar artery size.…”
Section: Sheath Sizementioning
confidence: 99%
“…16 However, the complication is not benign, as hand ischemia resulting from RAO has been reported. [17][18][19] Furthermore, once the artery is occluded, it cannot be used as an access site for future catheterization or as an arterial conduit for bypass surgery. RAO renders the ipsilateral ulnar artery unusable as well, because instrumenting and cannulating the ulnar would put the patient's hand at risk of ischemia.…”
mentioning
confidence: 99%
“…Intracardiac thrombus formation is a rare complication during angiography. Generally, local vascular complications occur less frequently with the radial artery access and even radial access is associated with better outcomes (2,3). Nevertheless, there is no information on other major complications in this arterial access way.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports on digital ischemia requiring amputation in patients with a negative AT [18,19]. Greenwood et al have investigated the effect of RA occlusion in patients previously screened by AT [20]. In this study RA was occluded for 30 minutes and patients were screened for hand ishaemia, UA flow and venous lactate level.…”
Section: Discussionmentioning
confidence: 99%